2020
DOI: 10.1038/s41593-020-0632-8
|View full text |Cite
|
Sign up to set email alerts
|

General anesthetics activate a potent central pain-suppression circuit in the amygdala

Abstract: General anesthesia (GA) can produce analgesia (loss of pain) independent of inducing loss of consciousness, but the underlying mechanisms remain unclear. We hypothesized that GA suppresses pain in part by activating supraspinal analgesic circuits. We discovered a distinct population of GABAergic neurons activated by GA in the mouse central amygdala (CeA GA neurons). In vivo calcium imaging revealed that different GA drugs activate a shared ensemble of CeA GA neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 54 publications
6
99
2
Order By: Relevance
“…In addition, ketamine is able to produce rapid antidepressant responses by inducing prefrontal cortex synaptogenesis and reversing the synaptic deficits caused by chronic stress [ 96 ]. A recent study has shown that ketamine is capable of activating GABAergic neurons in the central amygdala in both acute and chronic pain states [ 97 ]. Other regions such as the insular cortex, periaqueductal gray, and nucleus accumbens may also be involved in the anti-aversive effects of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ketamine is able to produce rapid antidepressant responses by inducing prefrontal cortex synaptogenesis and reversing the synaptic deficits caused by chronic stress [ 96 ]. A recent study has shown that ketamine is capable of activating GABAergic neurons in the central amygdala in both acute and chronic pain states [ 97 ]. Other regions such as the insular cortex, periaqueductal gray, and nucleus accumbens may also be involved in the anti-aversive effects of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Of these sub‐regions, the central nucleus of the amygdala has been identified as a key component in pain processing (Allen et al., 2020; Simons et al., 2014). Recent findings from rodents indicate the central nucleus serves a dual or bidirectional role with cells mediating inhibitory functions and others serving a facilitating function (Hua et al., 2020; Neugebauer et al., 2020; Wilson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…CeA PKCδ neurons and attenuate (rather than promote) pain-related behavior (Hua et al, 2020). CeA Sst neurons are also a good example of a "general encoding" population, since these neurons relate to appetitive stimuli (Kim et al, 2017;Wilson et al, 2019), but also contribute to the generation of defensive behaviors (Li et al, 2013;Penzo et al, 2015;Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%